Microsurgery Fellows' Impression of Clinical and Educational Offerings during Fellowship Year - Sullivan, Brianne J.; Maliha, Samantha; Henderson, Peter W. (Journal of Reconstructive Microsurgery, 2020)
Background Acquisition of microsurgical skill and clinical knowledge is the primary goal of a microsurgery fellowship. There has yet to be any comprehensive reporting in the literature of how American microsurgery fellows viewed their curricula and training at the conclusion of their fellowship year.Methods An anonymous, electronic survey was developed and distributed to all 2016 to 2017 microsurgery fellows (n = 37) at the U.S.-based microsurgery fellowship programs (n = 23). Qualitative questions were assessed using either a Likert-type scale of 1 (not at all) to 5 (very), multiple choice, or free response.Results Twenty-six of 37 fellows (70%) responded to the survey. Respondents reported a mean of 14.4 lectures offered, with a range of 0 to 100. Dry laboratory simulation training was formally incorporated into 32% of microsurgery fellowships and live animal simulation training was formally incorporated into 12%. The median number of free deep inferior epigastric perforator flap cases performed was 112.5, ranging from 60 to 230. A majority felt that an organized microsurgical educational curriculum would be “beneficial,” with 42% reporting that an organized microsurgery curriculum would be “very beneficial.” Twenty-six of the respondents (100%) said that they would choose to do a microsurgery fellowship again if given the choice.Conclusion Respondent data show that microsurgery fellows are satisfied with training, clinical experience is variable but adequate, educational experiences and opportunities vary from program to program, simulation skills training are perceived to be underutilized, and a program-organized microsurgery curriculum is believed to be advantageous to optimize development of technical and clinical skills.
Keywords: microsurgery; education; plastic; fellowship; curriculum